A Rare Presentation of Adductor Spasmodic Dysphonia: A Case Report - Hemalatha, Ganjala; Muskan, Shaik; Pragna, Gunde; Mitha, Pasam Madhu; Vinnakota, Dileep Kumar; Shaik, Uzma Aafreen; Jonnadula, Siva Bhanu; Mohana, Kollipara; Rao, Gajula Ram Nageswara (Indian Journal of Pharmacy Practice, 2026)
Adductor Spasmodic Dysphonia (AdSD) is a focal laryngeal dystonia characterized by involuntary contractions of the vocal fold adductor muscles, particularly the thyroarytenoid muscle, resulting in strained, effortful, and interrupted speech. It is the most common subtype of spasmodic dysphonia and is considered a neurological disorder involving dysfunction of central motor control pathways. We report a case of a 57-year-old female who presented with progressive dysphonia, throat discomfort, and vocal strain. Clinical evaluation and videolaryngostroboscopy revealed abnormal vocal cord movement consistent with AdSD. The patient was managed with botulinum toxin injection into the thyroarytenoid muscles along with supportive pharmacotherapy and surgical intervention (thyroplasty). The case highlights the importance of early diagnosis and evidence-based management of AdSD to improve voice quality and patient quality of life.
Keywords: Adductor Spasmodic Dysphonia; Dystonia; Videolaryngostroboscopy